PENERAPAN MODEL COOPERATIVE SNOWBALL THROWING UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS IV MIN 42 PIDIE - Zahrina (JURNAL EKSPERIMENTAL : Media Ilmiah Pendidikan, 2019)
This research wanted to identify whether the implementation of Cooperative Snowball Throwing could increase the achievements of the 4th grade students of MIN 42 Pidie. This research was a Classroom Action Research. The results described in qualitative data analyzing. It was found that the average scores of the students increased significantly in each cycle. Cycle I was 70.23, cycle II was 81,36 and cycle III was 87,27. Thus, the implementation of Cooperative Snowball Throwing could improve the students’ achievements in learning.